Pre-service early childhood educators’ attitudes toward supporting digital safety of preschool children - Zhanna Assankhanova; Assem Bulshekbayeva; Ulbossyn Kyyakbayeva; Kaliya Akhataeva; Nazira Atemkulova (Institute of Advanced Engineering and Science, 2026)
The readiness of preschool teachers to ensure children’s digital safety (DS) is currently one of the overarching challenges for early childhood education (ECE) systems. Unfortunately, developing countries, particularly Kazakhstan, do not necessarily possess the required resources to run preschool educational programs to ensure children’s DS. This study explores pre-service early childhood educators’ (PSECEs) cognitive, affective, and behavioral attitudes toward supporting DS of preschool children. It also considered PSECEs perceptions of their role and responsibility in supporting preschool children’s DS and their readiness to address these issues in their future professional practice. The research adopted a cross-sectional mixed-methods design without instructional intervention. The study was carried out at the Abai Kazakh National Pedagogical University in Almaty, Kazakhstan, with 344 participants in the experiment. The findings highlight the interrelated nature of cognitive, affective, and behavioral components of study participants’ attitudes. Study participants had strong affective engagement. However, the results revealed a noticeable imbalance between emotional concern and practical readiness. This research highlighted that DS content in preschool teacher education programs has not kept up to date with global digital advances. Consequently, there is a need to adopt coherent content of practice-oriented approaches to DS in preschool teacher education programs. This paper further extends the body of theory on PSECEs attitudes toward supporting DS of preschool children and provides new insights into the educator candidates’ cognitive, affective, and behavioral attitudes.